Economics and the public good the end of desire in Aristotle's politics and ethics - Pascarella, John Antonio (Economy, polity, and society (Rowman & Littlefield International), 2022)
"What is the relationship between politics and economics? Many of today's most pressing political issues are economic in nature. Whether it is the question of the distribution of wealth in society or the extent to which international commerce should be encouraged, politics and economics are inextricably linked in contemporary political discourse. Regardless of the particular questions at stake in these debates, there is a fundamental moral question at their foundation that is often ignored: What is the good of politics and economics? Though the different sides in debates about politics and economics often argue implicitly from the assumption that their approach is good, those engaging in the debate and their observers are surprisingly ill-equipped to engage the moral question itself. Aristotle's political philosophy, however, takes on this moral question directly. Through a careful inquiry into human nature and the many longings driving human beings - particularly for happiness and friendship - Aristotle shows the necessity for politics and economics to be understood in relation to a good that neither art can achieve on its own"--